IDENTIFIKASI SPESIES BEGONIA DI KAWASAN CAGAR ALAM GUNUNG NYIUT DESA PISAK KECAMATAN TUJUH BELAS KABUPATEN BENGKAYANG - Yusup, Dandi; Kartikawati, Siti Masitoh; Tavita, Gusti Eva (JURNAL HUTAN LESTARI, 2024)
Begonia is a herbaceous plant from the Begoniaceae family that grows in terrestrial and lithophytic habitats, i.e. lives on the banks of streams, limestone and sandstone and moist rock cliffs near airflow. Begonia plants can be found in lowland forests to hill forests. The distribution of begonias on the island of Borneo is estimated at 600 species. This study aims to identify the types of Begonias in the Gunung Nyiut Nature Reserve area, Pisak Village, Seventeen District, Bengkayang Regency by describing the morphological characteristics of the generative and vegetative organs. This study uses the exploratory method, namely exploring every corner of the research location that is in accordance with the object under study. Exploration was carried out by exploring research locations based on begonia habitats and by collecting and documenting the types of begonias found. The results of this study found 3 species of begonias, namely Begonia inobongensis Kiew., Begonia sp and Begonia congesta Ridl. Keywords: Begonia, Identification, Gunung Nyiut Nature Reserve. Abstrak Begonia merupakan tumbuhan terna dari famili Begoniaceae yang tumbuh pada habitat teresterial dan litofit, yaitu hidup pada tepian aliran sungai, batuan kapur dan batuan berpasir serta tebing-tebing batu yang lembab dekat aliran air. Cagar Alam Gunung Nyiut dengan hutan tropis dan keadaan ekosistem daerah rendah, ekosistem perbukitan serta tipe vegetasi tipe pegunungan yang berpotensi sebagai preferensi habitat begonia. Penelitian ini bertujuan untuk mengidentifikasi jenis Begonia pada kawasan Cagar Alam Gunung Nyiut Desa Pisak Kecamatan Tujuh Belas Kabupaten Bengkayang dengan mendeskripsikan ciri morfologi organ generatif dan vegetatif. Penelitian ini menggunakan metode eksplorasi yaitu menjelajahi setiap sudut lokasi penelitian yang sesuai dengan habitat begonia. Hasil yang diperoleh dari penelitian ini adalah ditemukannya 3 spesies begonia yaitu Begonia inobongensis Kiew., Begonia sp dan Begonia congesta Ridl. Kata kunci: Begonia, Identifikasi, Cagar Alam Gunung Nyiut.